Discrete variable design of frames subjected to seismic actions accounting for element slenderness. (15th January 2015) - Palizzolo, Luigi; Benfratello, Salvatore; Tabbuso, Pietro
Abstract: An optimal design problem formulation of elastic plastic frames under different combinations of fixed and seismic loads is presented. The optimal structure must behave elastically for the fixed loads, shakedown for serviceability conditions and prevent instantaneous collapse for fixed and high seismic loads. P-Delta effects and element buckling are considered. An appropriate modal technique is utilized. The design variables can have components in a continuous field or, alternatively, in chosen discrete sets or, yet, both kind of variables can be present. The design problem is formulated on the ground of a statical approach. The applications are related to steel frames.